Development of size-tunable polymeric nanoparticles for drug delivery applications - Sawasdee, Komkrich; Choksawad, Ployphailin; Pimcharoen, Sopida; Prapainop, Kanlaya (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Poly(lactide-co-glycolide) (PLGA) nanoparticles (NPs) have been widely used in drug delivery applications because of its excellent properties such as biocompatibility, biodegradability along with its abilities to deliver hydrophobic drugs, increase drug bioavailability, and improve drug absorption to targeted cells in both oral and parenteral administrations. The PLGA NPs can be synthesized using emulsion solvent evaporation method. Each parameter during synthesis play a role in formation of nanoparticles and could affect to form different NP sizes which is an important factor for successful development of drug delivery system. Aims: The aim of this study is to prepare different sizes of PLGA NPs by investigation of four factors (molecular weight (MW) of PLGA, emulsifier concentrations, organic solvent type and power of ultrasonication) that involve in PLGA nanoparticle synthesis.Methods: PLGA nanoparticles were prepared by emulsion solvent evaporation method. Size and size distribution were analyzed by dynamic light scattering and polydispersity index (PdI).Results: The effect of four parameters: PLGA MW, emulsifier concentrations, solvent types, and amplitude of ultrasonication on PLGA NPs preparation were evaluated. Changing one parameter results in different sizes of PLGA NPs varied from 150-300 nm. PdI which is an indicator for determination of size distribution of NPs are also varied with overall value less than 0.2.Conclusion: MW of PLGA polymer, emulsifier concentration, type of organic solvent and power of ultrasonication affect the size and size distribution of PLGA NPs.